2017
DOI: 10.1002/cssc.201700456
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Friendly Recycling of Fuel‐Cell Membrane Electrode Assemblies by Using Ionic Liquids

Abstract: The platinum nanoparticles used as the catalyst in proton exchange membrane fuel cells (PEMFCs) represent approximately 46 % of the total price of the cells for a large-scale production, and this is one of the barriers to their commercialization. Therefore, the recycling of the platinum catalyst could be the best alternative to limit the production costs of PEMFCs. The usual recovery routes for spent catalysts containing platinum are pyro-hydrometallurgical processes in which a calcination step is followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…It has been previously shown that the anodic signal observed in BMIM Cl for potential values was higher than 1 V vs. Ag +I /Ag, and the oxidation peak A1 recorded in 0.25 M BMIM Cl in BMIM TFSI corresponded to both of the two following oxidation reactions (8) [35,36] and (9), whose occurrence cannot be distinguished from each other in the voltammograms: The cathodic stability was identical for the three electrolytes, and limited by the reduction of the BMIM + cation [34] at −1.5 V vs. Ag +I /Ag. We have previously demonstrated that Pt cannot be oxidized in BMIM TFSI [32]. The oxidation signal observed at 2.8 V vs. Ag +I /Ag in BMIM TFSI and in the IL mixture corresponds then to the oxidation of the TFSI − anion [34] (7):…”
Section: Electrochemical Leaching and Electrodeposition Of Platinummentioning
confidence: 93%
See 4 more Smart Citations
“…It has been previously shown that the anodic signal observed in BMIM Cl for potential values was higher than 1 V vs. Ag +I /Ag, and the oxidation peak A1 recorded in 0.25 M BMIM Cl in BMIM TFSI corresponded to both of the two following oxidation reactions (8) [35,36] and (9), whose occurrence cannot be distinguished from each other in the voltammograms: The cathodic stability was identical for the three electrolytes, and limited by the reduction of the BMIM + cation [34] at −1.5 V vs. Ag +I /Ag. We have previously demonstrated that Pt cannot be oxidized in BMIM TFSI [32]. The oxidation signal observed at 2.8 V vs. Ag +I /Ag in BMIM TFSI and in the IL mixture corresponds then to the oxidation of the TFSI − anion [34] (7):…”
Section: Electrochemical Leaching and Electrodeposition Of Platinummentioning
confidence: 93%
“…1-butyl-3-methyl imidazolium bromide (BMIM Br) was prepared according to the procedure described in [31]. 1-butyl-3-methyl imidazolium bis(trifluoromethylsulfonyl)imide (BMIM TFSI) was also prepared as reported in [32].…”
Section: Chemicalsmentioning
confidence: 99%
See 3 more Smart Citations